Contrast blush on CT is a poor predictor of active bleeding on pelvic angiography. Issue 3 (December 2018) - Do, Andrew S.; Childs, Benjamin R.; Gael, Sarah; Vallier, Heather A.
Abstract: Objective: Determine if contrast extravasation (CE) on computed tomography (CT), also called CT blush, is a reliable predictor of clinically relevant arterial bleeding from pelvic ring injury. Design: Retrospective cohort. Setting: Single level I trauma center. Patients/participants: A total of 189 patients who underwent pelvic angiography between 1999 and 2015. Intervention: Demographic and injury data, including Young–Burgess fracture classification, Injury Severity Score (ISS), Glasgow Coma Scale (GCS), and clinical data including hypotension and heart rate upon presentation were recorded. Charts, radiographs, and interventional radiology reports and studies were reviewed. Main outcome measurements: CE on CT scan was noted from reports. Angiography studies were reviewed for active arterial bleeding. Results: Mean age was 49 years, with 64% male. CE was noted in 111 patients (66%), with increasing frequency over the study period. Patients under age 55 were less likely to have CE ( P < .001). GCS was higher and ISS lower in patients with CE (both P < .05). For CE as predictor of active bleeding, sensitivity was 67%, specificity 34%, and positive predictive value (PPV) was 58% ( P = .95). For CE as predictor of overall mortality, the sensitivity, specificity, and PPV were 67%, 33%, and 16%, respectively ( P = 1.0). However, hypotension had sensitivity of 83% for active bleeding and 97% for mortality, both P < .001. Conclusions: While CT blush was neither a sensitive nor specific predictor of active bleeding on pelvic angiography, hypotension was a sensitive indicator of both bleeding and mortality. These findings suggest that CE is not an independently sufficient indication for pelvic angiography. Level of Evidence: Level III